Tinjauan Hukum Ekonomi Syariah Terhadap Sistem Waralaba Es Teh Poci (Studi Kasus Es Teh Poci Geragai) - Sela Septiani Putri; Haeran Haeran; Hasna Dewi; Kurniawan Kurniawan; Alisyah Pitri; Reza Okva Marwendi; Ahmad Hidayat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the implementation mechanism of the Teh Poci Geragai franchise agreement and analyze it from the perspective of Sharia economic law. The study is motivated by the growth of the franchise system in Indonesia—which involves a cooperative agreement between the franchisor and franchisee—necessitating an assessment of its compliance with Sharia principles. This research employs a qualitative method with empirical and sociological approaches. Data were collected through observation, interviews, and documentation, then analyzed descriptively based on Sharia economic law principles and DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017 concerning the *Ijarah* (lease/service) contract. The findings indicate that the Teh Poci franchise system in Geragai utilizes a cooperative agreement incorporating elements of *ijarah* regarding the use of the brand and business system, alongside a sale-and-purchase agreement for the supply of raw materials. Such practices are fundamentally permissible under Sharia economic law as they satisfy the principles of mutual consent, contractual clarity, and a *halal* (permissible) business object. However, instances of non-compliance with the agreement's terms were identified, indicating that the implementation of the contract has not yet been optimal.